EPISTEMOLOGI FIKIH DI MEDIA SOSIAL (KONSTRUKSI EPISTEMOLOGIS FATWA MAJELIS ULAMA INDONESIA TENTANG BERMUAMALAH) - A’yun, Qurrota; Istiani, Nurul (Fakultas Agama Islam Universitas Wiralodra Indramayu, 2021)
This study intends to explore and identify the epistemological basis of Islamic law in the construction of the Fatwa Majelis Ulama Indonesia (MUI) Nomor 24 Tahun 2017 Tentang Hukum dan Pedoaman Bermuamalah Melalui Media Sosial. This qualitative research is in the form of a literature review with a normative philosophical approach. The analytical theory used is the paradigm of idealism and realism of Islamic law. The results show that the epistemological construction of Islamic law in the fatw MUI a on Law and Guidelines for Bermumalah Through Social Media integrates the tendencies of the idealism and realism paradigm of Islamic law. This can be seen from the various elements that underlie the construction of the epistemological building of the Fatwa MUI. First, universal ethical moral values ​​('am) which are taken from the theological text basis (nas). Second, the use of the rules of Islamic law (qawaid fiqhiyah) which emphasizes the rules of sadd al-zari'ah (preventive action) and maslahah mursalah (public benefit). Third, the opinion of classical scholars. Fourth, scientific explanations of expert opinions regarding the use of social media